PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN SMART APPS CREATOR PADA MATA PELAJARAN IPS - Ade Vidianti ade; Sulistia Kurnia Putri (JURNAL ILMIAH BETRIK, 2023)
This study aims to Develop Learning Media Based on Android using the Smart Apps Creator for Social Studies Clas V at Elementary School. The type of research use is Research and Development (R&D) research. The method use is a prosedural method with data collection techniques in the from of a questionnaire. From the evaluation results, media experts give a percentage of 87% in the “very good category”. Design experts give a percentage of 87% in the “very good category” and material experts give a percentage of 92% in the “very good category”. On product evaluation on an individual scale with the research object of 3 respondents namely class V.A student a percentage of 90,74% was obtained in the “very good category”. Small group evaluation with the research object of 6 respondents namely class V.B student obtained a percentage of 92,28% in the “very good category”. Than a large-scale evaluation was carried out with the object of research being 30 respondents namely class V.C student a percentage of 91,13% was obtained in the “very good category”. It can be concluded that this android based learning product is valid and feasibel to use in the field.